Environmentally friendly Finishing of Cotton Fabric via Star-like Silver micro/nano Particles Synthesized with Neem/Salep. Issue 10 (3rd October 2021) - Rohani Shirvan, Anahita; Kordjazi, Sheyda; Bashari, Azadeh
ABSTRACT: In this study, a novel silver solution was prepared by a simple green synthesis method using AgNO3, neem and salep extracts at room temperature. The results of UV-Visible spectrophotometer and Scanning Electron Microscopy (SEM) showed the formation of silver particles with a star-like morphology and sharp edges in the solution. In order to achieve an antibacterial cotton fabric, it was treated with the solution containing star-shaped silver particles by an impregnation method. Also, in order to change the surface charge of cotton fabric and more silver adsorption, a cationic surface modification was performed. Surface morphology and antibacterial properties of treated cotton fabric were characterized by SEM, inductively coupled plasma-optical emission spectrometer (ICP-OES), and antibacterial test based on the AATCC100 method, respectively. SEM images showed the presence of silver particles on the surface of treated fabric samples and ICP-OES determined the amount of silver content on the fabrics. In addition, the bacterial inhibition experiments demonstrated that the treated cotton fabrics with the star-like Ag particles synthesized by neem and salep have significant antibacterial properties against gram-positive and gram-negative bacteria. The utilized method was an easy, nontoxic, and environmentally friendly procedure for the preparation of antibacterial textiles with attractive feature in the medical and hygienic products.